Understanding Power in Ancient Egypt and the Near East, Volume 1 : Approaches - Thompson, Shane,; Tomkins, Jessica, (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2025, 2025)
This volume offers new theoretical approaches to the study of concepts and manifestations of power in the ancient world. Bringing together scholars from Egyptology and ancient Near Eastern studies, this volume aims to synchronize our understanding of the complex mechanics of Power across our fields. Broad in theoretical, geographical, and temporal scope, it presents theoretical models in an approachable manner, showcasing ways in which they can be employed by all scholars of the ancient world.